Every time you go away [large type] - Harbison, Elizabeth M. (Center Point Large Print, 2018)
"Three years after her husband's death, Willa returns to the beach house where he passed in Ocean City, Maryland, to sell it, but Ben's ghost keeps reappearing. Willa invites their son, her best friend, and her friend's daughter for one last summer at the beach as she says goodbye to her husband and reconnects with her son"--